Analisis Value for Money terhadap Kinerja Keuangan Pemerintahan Kota Depok Tahun Anggaran 2021-2023 - Verliana Diva; Sonny Fransisco Siboro; Anila Ambarani; Adella Yudanti (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
The aim of this research is to evaluate the financial performance of the Depok City Government in 2021-2023 based on value for money, namely in terms of economy, efficiency and effectiveness. The qualitative descriptive analysis method was used to carry out the analysis in this research. The performance of the Depok City Government is a source of output used to calculate efficiency values. The calculation compares input and output. While the output is the performance that has been achieved by the Depok City Government, the input is the economic value that has been obtained and the calculation of the effectiveness value is based on a comparison between the outcome and the output. Research findings show that the Depok City Government operated very economically from 2021 to 2023 based on its financial performance. The research findings indicate that the financial performance of the Depok City Government in terms of economic and effectiveness for the fiscal years 2021-2023 demonstrate stability, with an average achievement of 85.53% and 103.21% respectively. However, in terms of efficiency, the financial performance of the Depok City Government shows instability, with an average achievement of 84.44%. Therefore, the Depok City Government needs to make improvements to ensure that the efficiency level remains within a stable range.